« Ta en tê phonê » - Jean-François Savang (Carnets)
In this paper, we are going to question the voice as it’s represented in Aristotle’s Peri hermeneias. To be more exact, we focus on the expression « ta en tê phonê » which means « what is in the voice ». In fact, many translations give « what is in the voice » a determined sense as « words », « spoken sounds », « sound shapes » or merely « sound ». Nevertheless, voice’s expression in the Aristotle’s text refers to the undefinite « what », and therefore raises concerns about language indetermination in the voice, as both Henri Meschonnic and Georgio Agamben said. Meschonnic in particular, deductes from the critical Aristotle voice translation, the legacy of sign institution extended to the whole language.